Estudo químico de espécies de Cordia (Boraginaceae): Cordia multispicata (Cham.) e Cordia globosa (Jacq.) - Silva, Ana Karine Oliveira da (2013)
This work reports the chemical investigation of the hexane extracts from the roots of Cordia multispicata and Cordia globosa species. For the compounds isolation were used classic chromatographic techniques, such as open and “flash” chromatography on column over silica gel, molecular exclusion on sephadex LH-20 and High Performance Liquid Cromatography in reverse phase. The chemical investigation of the hexane extract of C. multispicata lead to the isolation of two known terpenoid naphthoquinones, the cordiaquinones B and J. In addition, the new naphthoquinone 6-[10-(12,12,16-trimethyl-7- oxabicyclo[2.2.1]hept-2-yl]-2,3-dihydroxy-1,4-naphthalenedione, which was designed cordiaquinone P. From the hexane extract of C. globosa were isolated two uncommon terpenec hydroquinones, (4bE,6Z,8E)-1,4-dihydroxy-9a,10-dihydro-10,12-epoxy-5- methylbenzo[a]azulen-12-one and 4bZ,6Z,8E)-1-hydroxy-9a,10-dihydro-4,11:10,12- diepoxy-benzo[a]-azulen-11,12-dione, both reported for the first time. The Nbenzoylphenylalaninyl-N-benzoyl-2-amino-3-phenylpropyl was also isolated. The cytotoxic potential of the new compounds were evaluated against three tumor cell lines OVCAR-8 (ovarium), SF-295 (glioblastoma) and HCT-116 (colon). The compounds were weakly active showing IC50 values > 5µg/mL. The structural elucidation was performed by spectrometric methods: IR, HRMS and 1H and 13C NMR, including bidimensional techniques (COSY, HSQC and HMBC), in addition to comparison with literature data, whenever available.